The role of serum vitamin D levels in vitiligo - Karagün, Ebru; Ergin, Can; Baysak, Sevim; Erden, Gönül; Aktaş, Habibullah; Ekiz, Özlem (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Vitiligo is a common acquired pigmentary skin disorder. Vitamin D is responsible for skin pigmentation, increases tyrosinase activity and melanogenesis, and exhibits immunoregulatory functions. Low levels of vitamin D are associated with many autoimmune diseases, including systemic lupus, diabetes mellitus, rheumatoid arthritis, multiple sclerosis and alopecia areata. Few reports have evaluated serum vitamin D levels in vitiligo patients, and their results are conflicting. Aim : To evaluate serum vitamin D levels of vitiligo patients and compare the results with controls. Material and methods : In total, 50 vitiligo patients and 47 controls were enrolled in the study. Vitamin D levels were measured from blood samples. Group comparisons were performed using appropriate statistical methods. Results : The patients had lower serum vitamin D levels than the controls, but this difference was not significant (p = 0.570). Conclusions : It remains unknown whether vitamin D deficiency causes vitiligo. Larger controlled studies are required to prove whether low circulating vitamin D is a causative factor in vitiligo.